DAS benchmarking methodology based on FWZIC II and FDOSM II to support industrial community characteristics in the design and implementation of advanced driver assistance systems in vehicles - Abdullah Hussein Abdullah Al-Amoodi (Tanjung Malim, 2023)
DAS benchmarking methodology based on FWZIC II and FDOSM II to support industrial community characteristics in the design and implementation of advanced driver assistance systems in vehicles by Abdullah Hussein Abdullah Al-Amoodi